Search 72,401 tutors FIND TUTORS
Search for tutors
Ask a question
0 0

Inverse Function

Tutors, please sign in to answer this question.

1 Answer

Given     f(x) = 6x -1 ,     find      f-1(x)     

First, let   f(x) = y

     y = 6x - 1

Replace every x with y and every y with x:

     x = 6y - 1

Solving this equation for y given you the inverse of the original function f(x):

     x + 1 = 6y - 1 + 1

     x + 1 = 6y

     (x + 1)/6 = (6y)/6

     (x + 1)/6 = y

Thus,

          f-1(x) = (x + 1)/6